Association Between Air Pollution and Acute Coronary Syndromes During Lockdown for COVID-19: Results From the Terni Hub Center - Arrivi, Alessio; Dominici, Marcello; Bier, Nicola; Truglio, Mauro; Vaudo, Gaetano; Pucci, Giacomo (Frontiers in Public Health, 2021)
Background: During the lockdown for COVID-19, a massive decrease in hospital admissions for acute coronary syndrome (ACS) and a drop in air pollution were both detected in Italy. Our aim was to investigate the possible association between these two events at the Province of Terni, one of the most polluted urban and industrial area in Central Italy. Methods: We analysed data of daily 24-hour urban air concentrations of particulate matter (PM)10 and PM2.5 from fixed station monitoring network located in the main city centers of the Terni province, and accesses for ACS at the catheterization laboratory of the Cardiological Hub Center of the Terni University Hospital during lockdown. A comparison was made with data corresponding to the same lockdown time period of years 2019, 2018 and 2017. Results: Invasive procedures for ACS decreased in 2020 (n=49) as compared with previous years (n=93 in 2019, n=109 in 2018, n=89 in 2017, p<0.001). Conversely, reductions in average PM10 (20.7 mcg/m3) and PM2.5 (14.7 mcgg/m3) in 2020 were consistent with a long-term decreasing trend, being comparable to those recorded in 2019 and 2018 (all p>0.05) and slightly lower than 2017 (p<0.05). The Granger-causality test demonstrated the lack of association between time-varying changes in air pollution and the number of procedures for ACS. Conclusions: Our results did not support the hypothesis that reduction in invasive procedures for ACS during lockdown was linked to an air cleaning effect. Reasons other than reduced air pollution should be sought to explain the observed decrease in ACS procedures.